Mengajarkan Shalat pada Anak Melalui Metode Demonstrasi, Tanya Jawab, dan Pembiasaan - Ainul Hasanah (Universitas Al-Hikmah Indonesia, 2018)
The purpose of this research is to know the form of teaching practice of praying in PAUD Al-Munawwarah Somalang, Pakong, Pamekasan in the effort to introduce fiqh for early childhood and is part of the aspect of early childhood religion and moral development. This research uses observation and interview method with descriptive analysis technique. The results showed that the form of teaching the practice of worship in Salaat Al-Munawwarah using three methods of demographic methods, frequently asked questions and habituation.